Inguinoscrotal hematocele of the newborn - Şencan, Aydın; Karaca, İrfan; Şencan, Arzu Bostancı; Mir, Erol (The Turkish Journal of Pediatrics, 2000)
Neonatal inguinoscrotal hematocele is a very rare disease of the first few days of life. The cause of this pathology is thought to be related with the umbilical plastic clamp, with an incorrect clamping technique or with the infant's lying over the clamp. Surgical treatment is not necessary as long as testicular torsion is excluded. In this report, three cases of inguinoscrotal hematocele diagnosed at surgical exploration in our clinic are reported and the literature reviewed.
Keywords: inguinoscrotal hematocele; hematoma; newborn